Response surface methodology for the design of malachite green dye removal by γ-Fe2O3 dispersed on reduced graphene oxide sheets - Liu Zhu; Anam Sana; Muhammad Tariq Qamar; Ali Bahadur; Guocong Liu; Mohammad Aslam; Ammar Zidan; İsmail Seçkin Çardaklı; Shahid Iqbal; Sajid Mahmood; Muhammad Saad; Khalid M. Alotaibi (Scientific Reports)
Abstract A nanocomposite composed of rGO and γ-Fe2O3 was prepared using ultrasonication for the adsorption of malachite green (MG) dye. The preferential plane diffractions at 2θ values of 35.54° and 26.45° about γ-Fe2O3 (311) and rGO (002) with 19.85 and 20.92 nm crystallite sizes, respectively confirmed the successful formation of nanocomposite nature of the adsorbent. Moreover, XPS and FTIR results also confirmed the composite formation due to the existence of peaks relevant to the composite’s components. The adsorbent’s surface charge (pHPZC = ~ 7.1) was also estimated using the salt addition technique. To minimize experiments and optimize adsorption parameters for the removal of MG by the nanocomposite at 25 °C, central composite design (CCD) using response surface methodology (RSM) was used. The optimal adsorption parameters obtained from the within-range numerical optimization based on 0.923 Derringer’s desirability function were 200 mg/100 mL dose, 80 ppm dye solution, 7.99 pH and 112.68 min. contact time for ~ 90% MG dye removal and 40.64 mg/g adsorption capacity (qm) by rGO/γ-Fe2O3. However, ~ 98% MG dye removal with 64.26 mg/g (qm) was achieved upon extended-range estimation of adsorption parameters. The adsorption data exhibited the best co-relationship with Freundlich isotherm and pseudo-2nd order kinetic model. According to a thermodynamic analysis, the MG adsorption process on the rGO/γ-Fe2O3 surface is exothermic, spontaneous, and less random. Moreover, the thermal stability, desorption, regeneration and reusability of rGO/γ-Fe2O3 nanocomposite were also explored. Finally, this study shows that RSM can be an excellent technique to optimize the dye adsorption process at industrial scale.